2015
DOI: 10.1186/s12879-015-0862-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of isoniazid, rifampicin, pyrazinamide and ethambutol in Indian children

Abstract: BackgroundThe available pharmacokinetic data on anti-tubercular drugs in children raises the concern of suboptimal plasma concentrations attained when doses extrapolated from adult studies are used. Also, there is lack of consensus regarding the effect of malnutrition on pharmacokinetics of anti-tubercular drugs in children. We conducted this study with the aims of determining the plasma concentrations of isoniazid, rifampicin, pyrazinamide and ethambutol achieved with different dosage of the anti-tubercular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 36 publications
3
40
1
2
Order By: Relevance
“…A proposed PZA adult target range of 20 to 60 g/ml has been suggested (23), but a study from Botswana showed that a C max of less than 35 g/ml was associated with a poor outcome in adult pulmonary TB patients (39). Our results were similar to other pediatric studies reporting peak concentrations of 34.6 to 47.8 g/ml when dosed at 30 to 40 mg/kg (8,13,28,32).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…A proposed PZA adult target range of 20 to 60 g/ml has been suggested (23), but a study from Botswana showed that a C max of less than 35 g/ml was associated with a poor outcome in adult pulmonary TB patients (39). Our results were similar to other pediatric studies reporting peak concentrations of 34.6 to 47.8 g/ml when dosed at 30 to 40 mg/kg (8,13,28,32).…”
Section: Discussionsupporting
confidence: 81%
“…The peak RMP concentrations of 4.0 and 2.2 g/ml for the two different RMP formulations, respectively, were similar to those reported in other pediatric studies, documenting low peak concentrations of 2.8, 2.9, 3.5, 3.8, and 3.9 g/ml following an oral administration of 10 to 20 mg/kg (27-31). Higher median RMP peak concentrations of 10 and 12 g/ml were achieved when dosed at 10 and 15 mg/kg (P ϭ 0.008), respectively, in Indian children (32). RMP mean peak concentrations of 6.4 and 11.7 g/ml, when dosed at 10 and 15 mg/kg (P ϭ 0.005), respectively, were observed in 11 South African children younger than 2 years of age using a different RMP formulation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…33 Data on the pharmacokinetics of TB medicines among malnourished children are also needed, as differences have been reported. [34][35][36][37] Further research into anti-tuberculosis treatment in the setting of malnutrition can guide the development of recommendations for the optimal timing for the initiation of treatment, dosing, and follow-up of children with malnutrition and TB.…”
Section: Public Health Actionmentioning
confidence: 99%